Kajian Psikologi Komunikasi: Respon Seniman Reog Ponorogo Jawa Timur terhadap Klaim Kesenian Reog oleh Malaysia - Restianto, Dio; Salisah, Nikmah Hidiati (Journal of Communication Studies, 2024)
The purpose of this research is to understand the influence of Malaysian news claiming Reog art as their cultural heritage on Reog artists in Ponorogo, East Java. This controversial news has caused cultural tension and nationalism, which then sparked strong reactions from the artist community and society in Indonesia. The research method used is qualitative method by analyzing Reog artists and related media content. The results of the research show that the news has psychological, emotional, and motivational impacts on Reog artists. It is hoped that this research can provide a deeper understanding of how foreign media news can affect cultural identity and creativity of local artists, as well as broader implications for the sustainability and protection of Indonesian cultural heritage. Keywords: reog artists, news, psychological impact